Pengaruh Fasilitas Prasarana Terhadap Kepuasan Pengunjung di Destinasi Wisata Pantai Ampenan, Kota Mataram - Sari, Pande Komang Dewi Intan Cahyani (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p24, 2023)
This study discusses the effect of infrastructure facilities on visitor satisfaction at Ampenan beach tourist destinations, Mataram City. The aim of this research is to examine and explain the effect of infrastructure facilities on visitor satisfaction at the Ampenan beach tourist destination, Mataram city. The population in this study were Ampenan beach visitors, the sample used was 100 respondents, the quantitative research method with sampling was carried out using a non-probability sampling technique with several criteria. Data analysis used validity, reliability, and simple linear regression tests. This study used research instruments in the form of questionnaires, observations, and interview. The results showed that the significance value of the influence of infrastructure facilities (X) on visitor satisfaction (Y) was 0.001 the t-table value was 1.985. So, there is a significant influence of infrastructure facilities on visitor satisfaction at Ampenan beach tourist destinations. Based on the results of the analysis and discussion above, it can be concluded that there is a positive and significant influence of infrastructure facilities on visitor satisfaction at the tourist destination of Ampenan Beach, Mataram City. Apart from that, there are several inhibiting factors in maintaining infrastructure facilities at the Ampenan Beach tourist destination, such as lack of support from the government and the community around the destination, lack of awareness of traders about cleanliness, and poor facility management. Keywords: infrastructure facilities, visitor satisfaction, Ampenan Beach